To study the effect of Introducing Reciprocal Inhibition in Physiotherapy Protocol - Dr Parmanand; Vivek Shrivastava (Innovative Research Thoughts, 2023)
Shoulder mobility is crucial for performing various daily activities, and restrictions in this range of motion can significantly impact an individual's ability to perform ADLs like combing, shaving, cooking , bathing, dressing ,driving etc. This study aims to systematically explore the efficacy of soft tissue gliding in improving both mobility and pain levels during shoulder abduction Soft Tissue Glides can be applied to treat the following conditions of Shoulder Joint : Tendinopathy1,2,3 Bursitis2 Adhesive Capsulitis4,6 Restricted Range of Motion4,5 Reducing Pain6,1 Shoulder pain constitutes a prevalent reason for visits to primary care and orthopaedic clinics worldwide. The prevalence of shoulder complaints is estimated to range from 7% to 34%, with shoulder impingement syndrome identified as a prominent underlying aetiology. Since its initial description in 1852, shoulder impingement syndrome has emerged as the foremost cause of shoulder pain, accounting for a substantial percentage, ranging from 44% to 65%, of all reported shoulder complaints.8